Effect of Competency, Work Motivation, Industrial Work Experience and Facilities on the Readiness of Work for Senior High School Graduates in Electro Expertise Programs - Mustikawanto, A. (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2019)
This study aims to determine the effect of competency on vocational readiness readiness, the effect of work motivation on vocational graduates' readiness, the influence of the internship experience on the work readiness, the influence of learning facilities on the work readiness, and the effect of competency, work motivation, internship experience and learning tools together on job readiness. The research method used in this study is by using descriptive research methods with quantitative approaches. The population of this study were all students of the Vocational Electrical Skills Program in West Java Province with sample of 604 students. Data collection uses the questionnaire method or questionnaire. The trial of the research instrument was carried out on students of SMK 1 Katapang as many as 60 students of class XII Industrial Electronics Expertise Program. The results of this study are competence, work motivation, the internship experience, and work practice experience has a positive and significant effect on the work readiness, and competency, work motivation, experience of internship and learning facilities together have a positive and significant effect on work readiness of vocational graduates these four variables together affect work readiness.